Islam: A Very Short Introduction - Ruthven, Malise (New York Oxford University Press, 2012)
Islam features widely in the news, often in its most militant forms, but few people in the non-Muslim world really understand its nature. Malise Ruthven's Very Short Introduction, offers essential insights into the big issues, provides fresh perspectives on contemporary questions, and guides us through the complex debates.
Includes Index and Illustrations.
Keywords: Islam